Ecology and biology of the Antarctic giant fish Dissostichus mawsoni (Pisces, Nototheniidae): reproduction, trophic role and migrations in the Ross Sea region - DI BLASI, DAVIDE (Università degli studi di Genova, 2021)
Three different studies have been implemented to fill gaps in the knowledge of the Antarctic toothfish (Dissostichus mawsoni) life cycle in the Ross Sea. First, presence, abundance and size distribution of toothfish in the shelf, in areas periodically covered by sea ice, were investigated by means of Baited Remote Underwater Video systems (BRUVs), an emerging technology never employed before in such kind of habitat. The study was developed from 2015 to 2018 in McMurdo Sound and Terra Nova Bay, it highlighted the efficacy of the methodology for investigating the species, recording dozens of fish of different sizes. We started to make some inferences on how environmental variables influence the distribution of the toothfish in shelf areas, but even more important, we established a working protocol useful for future works. The second section has been focused on the Second Winter Survey conducted in September-October 2019 onboard of a New Zealand fishing vessel with the aim to investigate toothfish reproductive biology, its spawning period and the eggs development and dispersion. The results obtained, combined with those from the First Winter Survey conducted in June-July 2016, allowed to have for the first time a picture of Antarctic toothfish reproduction: the spawning occurs in a wide area in correspondence of the Pacific Antarctic Ridge, it happens in the middle of the winter, and eggs set during all their development in the surface layer of the water column. The last part of the work put light on the fate of toothfish after spawning, a question arose from the observation of the high percentage of sensibly debilitated individuals (named “axe handle”) in the breeding ground. Samples of muscles from six individuals (two “axe handle” and two regular from the breeding area, and two regular from the shelf) were investigated with regard to lipid distribution and composition. The analysis led us to reason on lipid mobilization and usage as energy reserve and/or for neutral buoyancy for reproductive migration, how ...